Gentle remediation options for soil with mixed chromium (VI) and lindane pollution: biostimulation, bioaugmentation, phytoremediation and vermiremediation - Lacalle, Rafael G. (2020)
Gentle Remediation Options (GROs), such as biostimulation, bioaugmentation, phytoremediation and vermiremediation, are cost-effective and environmentally-friendly solutions for soils simultaneously polluted with organic and inorganic compounds. This study assessed the individual and combined effectiveness of GROs in recovering the health of a soil artificially polluted with hexavalent chromium [Cr(VI)] and lindane. A greenhouse experiment was performed using organically-amended vs. non-amended mixed polluted soils. All soils received the following treatments: (i) no treatment; (ii) bioaugmentation with an actinobacteria consortium; (iii) vermiremediation with Eisenia fetida; (iv) phytoremediation with Brassica napus; (v) bioaugmentation + vermiremediation; (vi) bioaugmentation + phytoremediation; and (vii) bioaugmentation + vermiremediation + phytoremediation. Soil health recovery was determined based on Cr(VI) and lindane concentrations, microbial properties and toxicity bioassays with plants and worms. Cr(VI) pollution caused high toxicity, but some GROs were able to partly recover soil health: (i) the organic amendment decreased Cr(VI) concentrations, alleviating toxicity; (ii) the actinobacteria consortium was effective at removing both Cr(VI) and lindane; (iii) B. napus and E. fetida had a positive effect on the removal of pollutants and improved microbial properties. The combination of the organic amendment, B. napus, E. fetida and the actinobacteria consortium was the most effective strategy.